Application of the oblique lateral interbody fusion technique in salvage surgery: technical note and case series - Han, Jialuo; Han, Shuo; Meng, Shengwei; Zhao, Xiaodan; Zhang, Hao; Guo, Jianwei; Xu, Derong; Liu, Houchen; Chen, Mingrui; Ma, Xuexiao; Wang, Yan (Frontiers in Surgery, 2023)
Objective: Oblique Lateral Interbody Fusion (OLIF) technique is a promising interbody fusion technique. This study summarizes the technical note of OLIF as a salvage surgery and the preliminary outcomes of a series of cases. Patients and Methods: Retrospectively reviewed patients with leg or back pain induced by pseudarthrosis or adjacent segment disease after PLIF/TLIF. These patients underwent salvage OLIF surgeries in ours institutions from January 2021 to March 2022. The variables including demographic, clinical, surgical, and radiological characteristics of the enrolled patients were recorded and analyzed. Results: 8 patients (5 females and 3 males; mean age 69.1 ± 5.7 years, range 63-80 years) were enrolled in this study. The mean operation time was 286.25 minutes (range: 230–440 min), and the estimated blood loss was 90 ml (range: 50–150 ml). Only one of the eight patients experienced a complication of lower limb motor weakness, which disappeared within 5 days after surgery. The latest data showed that the mean intervertebral space height was increased from 8.36mm preoperatively to 12.70mm, and the mean segmentary lordosis was increased from 8.92° preoperatively to 15.05°. Bone fusion was achieved in all 7 patients except 1 patient who was followed for only 3 months. The JOA scores for low back pain of all patients were significantly improved at the final follow-up. Conclusion: OLIF provides a safe and effective salvage strategy for patients with failed posterior intervertebral fusion surgery. Patients effectively achieved recovered intervertebral and foraminal height with no additional posterior direct decompression.